Novel Chat Sebagai Inovasi Media Pembelajaran Sosiologi Materi Bentuk Interaksi Sosial - Putra, Bima Sayoga; Soepriyanto, Yerry; Susilaningsih, Susilaningsih (Universitas Negeri Malang, 2022)
This research and development aims to produce a product in the form of novel chat media as an innovation in sociology learning media for the form of social interaction. Research and Development or research and development is one of the research methods in producing products. The development method used in the manufacture of the product is the Borg & Gall model that has been adapted to the needs of the developer (information search and collection, planning, product development, product feasibility testing, revision of product feasibility test results, field trials, and final product improvement) In its application, the novel chat media is a complement to the sociology learning process, which means that the media is programmed to complement the learning material that students receive in the classroom. The results of the product feasibility test that has been tested on product experts and material experts as well as field trials conducted on students show that the novel chat media gets a positive and feasible tanggapanse. So it can be concluded that the novel chat media can be used as a sociology learning medium, and with the novel chat media students have a sense of ease, attractiveness and motivation in learning.AbstrakPenelitian dan pengembangan ini bertujuan untuk menghasilkan produk berupa media novel chat sebagai inovasi media pembelajaran sosiologi materi bentuk interaksi sosial. Research and Development atau penelitian dan pengembangan merupakan salah satu metode penelitian dalam menghasilkan produk. Metode pengembangan yang dipakai dalam pembuatan produk adalah model Borg & Gall yang telah disesuaikan oleh kebutuhan pengembang (pencarian dan pengumpulan informasi, perencanaan, mengembangkan produk, uji kelayakan produk, revisi hasil uji kelayakan produk, uji coba lapangan, dan penyempurnaan produk akhir). Dalam penerapannya media novel chat menjadi pelengkap dalam proses pembelajaran sosiologi, yang berarti media diprogramkan untuk melengkapi materi pembelajaran yang diterima siswa di dalam kelas. Hasil dari uji kelayakan produk yang telah diujikan kepada ahli produk dan ahli materi serta dilakukan uji coba lapangan kepada siswa, menunjukkan bahwa media novel chat mendapatkan tanggapan positif dan layak. Sehingga dapat disimpulkan bahwa media novel chat dapat digunakan sebagai media pembelajaran sosiologi, serta dengan adanya media novel chat siswa memiliki rasa kemudahan, kemenarikan dan motivasi dalam pembelajaran.